Improvement of Recursive DFT for APF With Higher Switching Frequency to Suppress Wideband Harmonics - Bingyuan Yang; Ke Dai; Chaowei Yang; Hui Luo; Kuan He; Ziwei Dai (IEEE Access, 2021)
Shunt active power filter (APF), with higher switching frequency, has a potential market for suppressing wideband harmonics in the more electric aircraft (MEA) or high-speed train (HST) power grid. In this case, the selective extraction of harmonic current reference is essential. Recursive discrete Fourier transform (RDFT) is widely adopted for its excellent selectivity and low computational burden. However, RDFT is tough to implement in the higher frequency APF with the shorter switching cycle, and suffers from the demerit of slow dynamics. To alleviate those, three improved RDFTs are proposed in this paper. Firstly, it is revealed that RDFT can be regarded as a series of DFT and inverse-DFT (IFT), and its settling time depends on the comb filter of DFT. Then, by rearranging the sampling frequency of DFT according to the extracted harmonic, the computational burden of twice-sampling RDFT (TS-RDFT) is reduced while satisfying the same extraction accuracy. Furtherly, to improve the dynamics of TS-RDFT while retaining the merits of simplicity and selectivity, the comb filter is reconfigured based on the load current spectrum. For balanced loads, the settling time of TS-RDFT can be shortened from 1 to 1/6 fundamental cycle in the synchronous reference frame. For unbalanced loads, it is shortened to 1/2 cycle in the $α β $ frame. Finally, the simulations with Matlab for harmonic extraction in 400Hz grid and the experiments with the APF prototype for harmonic suppression in 50Hz grid are carried out to verify the effectiveness of the proposed methods.